Kepemimpinan Unggul Kaprodi HKn/PPKn Dalam Upaya Membentuk Budaya Berkarakter Di Lingkungan Perguruan Tinggi - Bagus Subambang; Indra Lesmana (Universitas Negeri Malang, 2023)
Abstract: Character is a manifestation of a person's behavior that affects human life in establishing relationships with others. This study aims to describe the superior leadership of the Head of HKn / PPKn Study Program in an effort to form a culture of character in the university environment. This research uses a qualitative descriptive approach with case studies. Data collection was conducted using in-depth interview techniques, participant observation, and documentation studies. Informants in research consist of heads of study programs and lecturers who are key informants. In determining the informant, researchers used the snowball sampling technique. Data analysis in this study used two stages, namely individual data analysis with modified analytical induction methods and cross-site analysis. Checking the validity of the data used in this study includes the degree of trust, transferability, dependence, and certainty. The results of this study show that the Head of Study Program conducts socialization related to the development of character values to lecturers, staff and students. Furthermore, the Head of Study Program makes himself a good example by displaying behavior in accordance with established ethical and moral standards and paying attention to the self-development of lecturers, staff, and students based on character values.Keywords: Superior Leadership, Character Education, Culture of Character, College